Penerapan Metode Group Investigation dan Problem Based Learning Terhadap Kemampuan Berpikir Kritis Dengan Gaya Belajar Sebagai Variabel Moderasi - Iskandar Iskandar; Desi Kurnia; Sri Mulyati (Universitas Negeri Surabaya, 2023)
Critical thinking is crucial for students. One of the efforts to improve critical thinking through learning changes is by applying group investigation (GI) and problem-based learning (PBL) methods. This study aims to determine the effect of applying the GI and PBL methods on students' critical thinking skills with learning styles as the moderator variable. The research method was quasi-experimental with a 2 x 3 factorial design. The research subjects were class X students of Cilimus Vocational School, class of 2018-2019. This study used two-way ANOVA with SPSS 21 to analyze the data. The results showed that GI and PBL significantly affected students' critical thinking skills. It can be seen that (1) the GI learning method is more effective than the PBL learning method; (2) students' learning styles (visual, auditory, and kinesthetic) have no effect on student's critical thinking skills. Likewise, students' learning styles do not affect students' critical thinking skills; (3) There is no relationship between interactive learning methods and learning styles to increase students' critical thinking. In other words, learning styles do not strengthen or weaken the effect of applying experimental learning methods to improve student's critical thinking skills